Pengobatan Tradisional untuk Ibu dan Bayi Pasca Melahirkan pada Masyarakat Kota Semarang - Islamy, Cindy Fa'era; Husain, Fadly (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2026)
Traditional medicine is a cultural heritage that has been used for generations by the people of Genuk District, Semarang City. The people of Semarang City still maintain traditional medicine practices, one of which is the tradition of traditional medicine for mothers and babies after childbirth. The persistence of this traditional medicine practice is based on the fact that the postpartum phase is a crucial phase for mothers and babies. In addition to being considered to have fewer side effects than modern medicine, traditional medicine also reflects respect for local traditions in the community. This study aims to describe the classification of "dukun bayi" who practice traditional medicine, describe the traditional postpartum medicine practices carried out in Genuk District, Semarang City, and to determine the perceptions and beliefs of the local community regarding traditional medicine. The research method used in this study was a descriptive qualitative method involving in-depth interviews with informants, observation, and documentation. Data analysis was carried out in three ways, namely data reduction, data presentation, and conclusion drawing. The results of the study show that traditional postpartum care practices in Genuk District, Semarang City, are performed by two practitioners, namely “terapis bayi” and “dukun bayi”. By using existentialism theory, this study reveals that traditional healing is perceived, interpreted, and practiced by the people of Semarang City as part of their cultural identity amid modernization.